ASSOCIATION OF PREVASCULAR VITREOUS FISSURES AND CISTERNS WITH VITREOUS DEGENERATION AS ASSESSED BY SWEPT SOURCE OPTICAL COHERENCE TOMOGRAPHY. Issue 9 (September 2015) - Pang, Claudine E.; Schaal, Karen B.; Engelbert, Michael
Abstract : Purpose: To demonstrate the presence of prevascular vitreous fissures (PVF) and posterior vitreous cisterns in vivo and correlate with the degree of vitreous degeneration (VD). Methods: This was a cross-sectional study using Topcon Deep Range Imaging OCT-1 Atlantis 3D swept source optical coherence tomography for acquiring scans of posterior vitreous covering an 18 × 18-mm area in 104 eyes of 52 healthy volunteers without posterior vitreous detachment. Results: We observed that increasing age was associated with higher VD grades ( P < 0.05). Prevascular vitreous fissures, characterized by areas of lower optical density overlying the retinal blood vessels, were identified in 93 (89%) eyes, and the presence of PVF correlated with lower VD grades ( P < 0.05). Presence of cisterns correlated with higher VD grades ( P < 0.05). All eyes with absence of PVF were found to have established cisterns. Prevascular vitreous fissures were connected with cisterns in 44 of the 71 (62%) eyes with cisterns, while the base of the cistern was directly above retinal blood vessels in 38 (54%) eyes, which suggests that the cisterns could be derived from PVF. Conclusion: Swept source optical coherence tomography imaging can identify PVF and cisterns occurring in the context of age-related VD, and PVF appeared to be possible precursors of cisterns. Abstract : Swept source optical coherence tomography was able to characterize posterior vitreous cisterns and prevascular vitreous fissures in vivo and showed that cisternal spaces probably occur as a result of vitreous degeneration while prevascular vitreous fissures may be precursors of cisterns.